Oil Plants in Hittite Anatolia - Güterbock, Hans G.
GIŠSERDU “olive”; GIŠšаmаmа “a kind of nut”; GIŠliti- perhaps almond; ŠE.GIŠ.Ì probably read šapšama- in Hittite, “sesame” according to the traditional translation.